Root- And foliar-applied silicon modifies C: N: P ratio and increases the nutritional efficiency of pre-sprouted sugarcane seedlings under water deficit - Teixeira, Gelza Carliane Marques [UNESP]; de Mello Prado, Renato [UNESP]; Rocha, Antonio Márcio Souza [UNESP]; de Cássia Piccolo, Marisa (Public Library of Science (PLoS), 2020)
Water deficit limits the establishment of sugarcane plants from pre-sprouted seedlings (PSS). Silicon (Si) can mitigate such stress, and your supply in plants with the active absorption mechanism is carried out through roots. However, foliar spraying has been practiced to supply Si in PSS production nurseries. Althought it is known that Si via roots can alter C: N: P ratios, nothing has been reported about its supply via foliar spraying, nor whether such changes interfere with structural nutrient use efficiency and with plant physiological responses. Thus, this study aimes to asses whether Si foliar spraying changes C: N: P ratios and increases the nutritional efficiency of PSS, as well as whether water deficiency interferes with such a relationships. For these purposes, three experiments were carried out. In experiment I, treatments consisted of two sugarcane cultivars (CTC 4 and RB 966928) and three Si supply forms (in nutrient solution via roots [SiR], via foliar spraying [SiL], and one control with the absence of Si [-Si]). The same Si supply forms were used in the other two experiments. In experiment II, a short-term water deficit was induced by polyethylene glycol addition to nutrient solution (-0.6 MPa) for three days. In experiment III, a long-term water deficit was imposed using levels of soil water retention capacity (70% [no water deficit], 50% [moderate water deficit], and 30% [severe water deficit] for 30 days. Our findings revealed that Si supply decreased C concentrations regardless of water conditions and that N and P concentrations varied with Si supply form and water deficit level. Moreover, root- and foliar-applied Si modified the C: N: P stoichiometry and increased C use efficiency in PSS, which thus increased N and P use efficiencies. Such an increased nutritional performance helped adjust physiological parameters and increase dry matter yield in PSS, both under water stress and non-stress conditions. Further, Si foliar spraying promoted structural effects on PSS regardless of water conditions, even if sugarcane has an active absorption via roots. In conclusion, foliar spraying can be used to supply Si in PSS production nurseries.